Financial mechanisms and investment frameworks for renewables in developing countries (International Renewable Energy Agency, 2012)
The global financial system today is highly complex and, in the wake of the 2008 financial crisis and the on-going eurozone crisis, politically sensitive. Markets are in a risk-averse period. Meanwhile, RE markets overall are still relatively young and fluctuating. They comprise a variety of technologies and sub-sectors at different stages of maturity, and with distinct financing needs. The complexities of these two fields, added to the normal (and often unpredictable) pressures of politics in developing countries, pose an especially daunting challenge for policy makers. This report aims to help relieve some of this pressure by providing up-to-date analysis, recommendations and, where possible, improve clarity for policy makers regarding RE finance. It presents qualitative and quantitative analyses of financing trends and mechanisms, investment frameworks, policies, and enabling conditions for RE in the developing world.